Analisis Pembelajaran IPA Secara Daring pada Masa Pandemi Covid-19 - Novia Amarta Handayani*; Jumadi Jumadi (Universitas Syiah Kuala, 2021)
The emergence of Covid-19 in Indonesia has an impact on science learning activities in junior high schools, so that, it is transferred to learning online. This study aims to analyze online learning activities, supporting factors, inhibiting, and the effectiveness of online learning during the Covid-19 pandemic. It was conducted in SMP Negeri 2 Bungkal from October to November 2020. This study used descriptive qualitative methods to provide an overview of online learning at SMP Negeri 2 Bungkal. This study used semi-structured interview data given to science teachers, students, and students' parents. Data analysis used the analysis technique of Miles Huberman (1992) through three stages, namely data reduction, data display, and conclusion drawing/verification. The result of this study indicates the Covid-19 pandemic had an impact on learning activities. Online learning was carried out using Google Meet, Google Classroom, and WhatsApp media. Supporting and inhibiting factors in online learning, which are communication tools, internet networks, student motivation, and support from parents. Online learning is less effective because the material is not conveyed entirely to students. Most activities are carried out just by providing material and assignments and collecting assignments